ANALYSIS OF FAMILY PLANNING SERVICES FOR COUPLES OF REPRODUCTIVE AGES TOO YOUNG, TOO OLD, TOO CLOSE, AND TOO MANY (4T) WITH THE MATERNAL MORTALITY - Tahlillarani Widhianingrum; Devi Arine Kusumawardani; Sofiyanti Miftakhurohmah (Poltekkes Kemenkes Semarang, 2023)
Mothers who are too young, too old, have too many children or have birth spacing that is too close (mothers with 4T) are at a higher risk of experiencing maternal mortality. At the same time, the use of contraceptives in this group to prevent pregnancy was still low. This study aims to analyze family planning services for couples of reproductive age with 4T and cases of maternal death. This research method is quantitative and descriptive, using 58 data on reports of maternal deaths in Jember Regency for 2022. The study indicates that there are 20 (34.48%) maternal death cases that have at least one of the 4T criteria, with details of 10.34% of deaths in too young criteria, 15.51% of death in too old criteria, 8.60% of deaths in too many criteria; and 8.60% death in too close criteria. There were 20.69% of cases of death in unwanted pregnancies. The average achievement of family planning services for mothers with 4T is only 9.51%. This research can be used as material for evaluating family planning services for women with 4T so that it can reduce maternal mortality in Jember Regency